A Study on the Motivation of Lao Students to Learn Chinese in a Non-Target Language Learning Environment: A Case Study of Soochow University in Laos - Zhou, Xixing (Journal of Ecohumanism, 2025)
With globalization and the growing number of Chinese learners worldwide, second language acquisition has become a key focus in Chinese international education. Learning motivation is a critical factor in this process; however, empirical research on the motivation of Lao students to learn Chinese remains underexplored. This study sought to investigate the characteristics and factors of Lao students’ motivation to learn Chinese through a mixed-methods approach, including questionnaires and semi-structured interviews. Data were collected from 120 learners at Soochow University in Laos, with 12 participants engaging in interviews. Analysis methods included thematic analysis and analysis of variance. The findings revealed that (1) most students demonstrated beginner to intermediate proficiency, with short learning durations and vocabulary challenges; (2) statistical analysis showed a significant correlation between age and motivation (P = 0.003), while Chinese proficiency levels, gender, and other factors had no significant impact (P > 0.05); (3) Semi-structured interviews further revealed varied motivational orientations among learners in educational and professional contexts. Based on these findings, the study offers practical recommendations, including optimizing classroom instruction, enriching extracurricular activities, and enhancing cross-cultural teaching skills, to better support Chinese language learning in non-target language environments.